Prevalence of noncommunicable diseases and developmental conditions in 5014 Australian adolescents, and their correlations with diet, other lifestyle behaviours and mental health - Bridie Osman; Matthew Sunderland; Emma K. Devine; Louise Thornton; Felice Jacka; Maree Teesson (Australian and New Zealand Journal of Public Health)
Objective: Amongst Australian youth, there is currently a lack of understanding of the prevalence of noncommunicable diseases and developmental conditions and links with modifiable lifestyle behaviours, mental health and other socio-demographics. This paper aims to address this gap. Methods: Australian adolescents (N = 5014, Mage=14.7, SD=0.80) completed a self-report survey assessing noncommunicable diseases/developmental conditions, sex, socio-economic status (SES), lifestyle behaviours and mental health. Multivariable logistic regressions were used to estimate the associations between these variables. The moderating effects of sex and SES were investigated by including interaction terms in each regression model. Results: 45.6% adolescents reported ≥1 noncommunicable disease/developmental condition. Being female, consuming more sugar-sweetened beverages, ultra-processed foods, or alcohol, participating in more screen time, having depression, anxiety or psychological distress were each associated with higher rates of having at least one disease/condition (p<0.01). Sex and SES significantly moderated the associations between some lifestyle behaviours and eight diseases/conditions were examined. Conclusion: Australian adolescents experience considerable rates of noncommunicable diseases and developmental conditions, highlighting the significance of this public health issue. Implications for public health: Links with lifestyle behaviours and mental health highlight their potential importance in public health to assist with prevention and treatment of these common and emerging noncommunicable diseases and developmental conditions in adolescents.